Finding Antarctica's Pole of Inaccessibility. (18th October 2021) - Rees, Gareth; Gerrish, Laura; Fox, Adrian; Barnes, Richard
Abstract: Antarctica's Pole of Inaccessibility (Southern Pole of Inaccessibility (SPI)) is the point on the Antarctic continent farthest from its edge. Existing literature exhibits disagreement over its location. Using two revisions of the Scientific Committee on Antarctic Research's Antarctic Digital Database, we calculate modern-day positions for the SPI around 10 years apart, based on the position of the "outer" Antarctic coastline, i.e. its boundary with the ocean. These show that the position of the SPI in the year 2010 was around 83° 54' S, 64° 53' E, shifting on the order of 1 km per year as a result of changes of a similar magnitude in the Amery, Ronne-Filchner and Ross Ice Shelves. Excepting a position of the SPI calculated by British Antarctic Survey in 2005, to which it is very close, our newly calculated position differs by 150–900 km from others reported in the literature. We also consider the "inner" SPI, defined by the coastline with floating ice removed. The position of this SPI in 2010 is estimated as 83°37' S, 53° 43' E, differing significantly from other reported positions. Earlier cartographic data are probably not sufficiently accurate to allow its rate of change to be calculated meaningfully.